1998
DOI: 10.1088/0957-4484/9/3/013
|View full text |Cite
|
Sign up to set email alerts
|

Towards a light-addressable transducer bacteriorhodopsin based

Abstract: Highly oriented bacteriorhodopsin films were deposited using a specially designed procedure of electric field assisted monolayer formation. The self-assembly of the monolayer at the air/water interface was monitored by the increase of the surface pressure. The monolayers were transferred onto solid substrates by the Langmuir-Schaefer technique. Electrical measurements on the films with a specially designed chamber confirmed the improved orientation of the films. Possible application of the films in practical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Bacteriorhodopsin (bR) and other light‐sensitive proteins, including visual pigments (rhodopsin) from bovine,1–4 photosynthetic reaction centers5 are of interest for use in biotechnology and molecular electronic applications 6–10. The unique combination of photochromic, photoelectric and electrooptical properties of these proteins is of great fundamental and applied interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriorhodopsin (bR) and other light‐sensitive proteins, including visual pigments (rhodopsin) from bovine,1–4 photosynthetic reaction centers5 are of interest for use in biotechnology and molecular electronic applications 6–10. The unique combination of photochromic, photoelectric and electrooptical properties of these proteins is of great fundamental and applied interest.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriorhodopsin (bR) and other light-sensitive proteins, including visual pigments (rhodopsin) from bovine, [1][2][3][4] photosynthetic reaction centers 5 are of interest for use in biotechnology and molecular electronic applications. [6][7][8][9][10] The unique combination of photochromic, photoelectric and electrooptical properties of these proteins is of great fundamental and applied interest. bR is a promising candidate for information processing because of its astonishing stability against chemical, thermal and photochemical degradation as well as its efficient photochemistry and excellent reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…As theˇrst step, we build a 3D model of octR using bovR as a template, and compare it with the structure of bR. We also discuss this comparison in terms of nanotechnology applications that have been reported for bR [31] but can also be implemented in octR. We also built a model for mutant protein aimed at ocrR/bR interconversion.…”
Section: Introductionmentioning
confidence: 99%
“…21 The importance of active transport systems has led to the isolation and detailed study of several transporter proteins such as bR and their reconstitution in liposomes, vesicles, and supported lipid bilayers. 22,23 Recently, Luo et al demonstrated the immobilization and functionality of proteoliposomes ͑bR containing liposomes͒ in silica matrices. 15 Gramicidin, a model ion channel, is an unusual transmembrane peptide, with alternating D and L amino acids.…”
Section: Introductionmentioning
confidence: 99%